ANALYSIS OF STUDENTS' MISCONCEPTIONS ON PRIME NUMBERS BASED ON THE CERTAINTY OF RESPONSE INDEX (CRI) - Aisya Nabila Putri; Amelia Cristy Saragih; Mutia Hafiza; Rifka Elianti Br Kaban; Samuel Yordan Ambarita; Budi Halomoan Siregar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Misconceptions are one of the common problems in mathematics learning and can hinder students’ conceptual understanding. In the topic of prime numbers, misunderstandings often occur because students do not fully comprehend the definition and characteristics of the factors of a number. Therefore, a systematic identification is needed to determine the types of misconceptions experienced by students. This study aims to analyze students’ misconceptions on the topic of prime numbers using the Certainty of Response Index (CRI) method. This study employed a quantitative approach with a descriptive research design. The research subjects were 23 ninth-grade students at SMP Deli Murni Sukamaju. Data were collected through a diagnostic test consisting of 15 questions equipped with a CRI scale to measure students’ confidence in their answers. The data were analyzed by grouping students’ responses based on answer accuracy and confidence level, which were then classified into four categories of understanding: conceptual understanding, misconception, lack of understanding, and guessing. The results showed that out of 345 student responses, 31.6% were categorized as understanding the concept, 39.1% experienced misconceptions, 20.9% did not understand the concept, and 8.4% answered by guessing. The dominant misconceptions were related to the definition of prime numbers, determining the factors of a number, and the assumption that all odd numbers are prime numbers. These findings indicate that the CRI method is effective in identifying students’ misconceptions and can serve as a basis for teachers to design learning strategies that emphasize conceptual understanding. ABSTRAK Miskonsepsi merupakan salah satu permasalahan yang sering muncul dalam pembelajaran matematika dan dapat menghambat pemahaman konsep siswa. Pada materi bilangan prima, kesalahan pemahaman sering terjadi karena siswa belum sepenuhnya memahami definisi dan karakteristik faktor suatu bilangan. Oleh karena itu, diperlukan identifikasi yang sistematis untuk mengetahui bentuk miskonsepsi yang dialami siswa. Penelitian ini bertujuan untuk menganalisis miskonsepsi siswa pada materi bilangan prima dengan menggunakan metode Certainty of Response Index (CRI). Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian deskriptif. Subjek penelitian adalah 23 siswa kelas IX di SMP Deli Murni Sukamaju. Data dikumpulkan melalui tes diagnostik sebanyak 15 soal yang dilengkapi dengan skala CRI untuk mengukur tingkat keyakinan siswa terhadap jawaban yang diberikan. Data dianalisis dengan mengelompokkan respons siswa berdasarkan ketepatan jawaban dan tingkat keyakinan, kemudian diklasifikasikan ke dalam empat kategori pemahaman, yaitu memahami konsep, miskonsepsi, tidak memahami konsep, dan menebak. Hasil penelitian menunjukkan bahwa dari 345 respons siswa, sebesar 31,6% termasuk kategori memahami konsep, 39,1% mengalami miskonsepsi, 20,9% tidak memahami konsep, dan 8,4% menjawab dengan menebak. Miskonsepsi yang dominan berkaitan dengan definisi bilangan prima, penentuan faktor bilangan, serta anggapan bahwa semua bilangan ganjil adalah bilangan prima. Temuan ini menunjukkan bahwa metode CRI efektif untuk mengidentifikasi miskonsepsi siswa sehingga dapat menjadi dasar bagi guru dalam merancang pembelajaran yang lebih menekankan pada pemahaman konsep.